2005
DOI: 10.1021/jp0526243
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Approach to Understanding Macrolide−Ribosome Interactions:  NMR and Modeling Studies of Oleandomycin and Its Derivatives

Abstract: The three-dimensional structures of oleandomycin (1) and its derivatives oleandomycin-9-oxime (2) and 10,11-anhydrooleandomycin (3) were determined in different solvents by the combined use of NMR and molecular modeling methods. The experimental NMR data were compared with the results of molecular modeling and known crystal structures of the related molecules. It was shown that the dominant conformation of the lactone ring is the folded-out conformation with some amounts of the folded-in one depending on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 32 publications
2
32
0
Order By: Relevance
“…The macrolides and the keto derivatives, the ketolides, act by binding in the peptide exit tunnel of the ribosome (125,147,273,341) and thus preventing the growing peptide chain from vacating the peptidyltransferase center of the ribosome. This is believed to "gum up" the ribosome and prevent the further elongation of the nascent peptide chain.…”
Section: Inhibition Of Protein Synthesismentioning
confidence: 99%
“…The macrolides and the keto derivatives, the ketolides, act by binding in the peptide exit tunnel of the ribosome (125,147,273,341) and thus preventing the growing peptide chain from vacating the peptidyltransferase center of the ribosome. This is believed to "gum up" the ribosome and prevent the further elongation of the nascent peptide chain.…”
Section: Inhibition Of Protein Synthesismentioning
confidence: 99%
“…Novak et al [146][147][148][149][150] have shown that a systematic approach combining NMR and molecular modelling calculations could be applicable to conformational studies of free and bound macrolides and their interactions with ribosomes. Their results [146][147][148][149][150], and those of other groups [151][152][153][154][155], have shown that macrolides adopt two major conformational families, folded-out and folded-in, referring to the outward and inward folding of the ring fragment 3C-5C ( Figure 5.10).…”
Section: Macrolide-ribosome Interactionsmentioning
confidence: 99%
“…Conformational studies on macrolides [12][13][14] have shown the existence of two major conformational families: folded-out and folded-in, referring to the outward and inward folding of the macrocycle ring fragment C3-C5. Those studies demonstrated that vicinal coupling constants 3 J H2H3 and NOE proton-proton contacts H4-H11 and H3-H11, respectively, can serve as good indicators of the ring folding.…”
Section: Structural Elucidationmentioning
confidence: 99%